Determinants of Corporate Governance on Bank Financial Performance Through Green Banking in Indonesia - Ibram Pinondang Dalimunthe; Hari Gursida; Yohanes Indrayono (Journal of World Science, 2025)
This study aims to examine and analyze the influence of audit fees and auditor professionalism on audit quality, with auditor work experience as a mediating variable. The research is motivated by the importance of audit quality in enhancing the transparency and credibility of financial reporting, as well as the critical role of auditor experience in strengthening the relationship between audit fees, professionalism, and audit quality. The study was conducted on auditors working in Public Accounting Firms (PAFs) across Indonesia using a quantitative approach. Data were collected through questionnaires distributed to active auditors, and analyzed using path analysis. The results indicate that both audit fees and auditor professionalism have a positive and significant effect on audit quality. Moreover, auditor work experience significantly mediates the relationship between audit fees and professionalism with audit quality. These findings provide valuable implications for PAFs to improve audit quality through fair audit fee structuring, enhancement of auditor professionalism, and the development of work experience through continuous training.